Commitment or Compliance? Institutional Logics of Work Environment Management - Madsen, Christian Uhrenholdt; Hasle, Peter (Nordic Journal of Working Life Studies, 2017)
Scholars of the work environment have pointed out how management ideas and practices inspired by a human resource approach are influencing the work environment efforts in Nordic organiza tions. In this paper, we use the ‘institutional logics’ perspective to propose heuristic ideal types of two institutional logics of work environment management:The logic of compliance as the ideal type of the ‘traditional’ approach to work environment management and the logic of commitment as the human resource informed approach. Through a side-by-side comparison of key characteristics, we analyze the two ideal types as instantiations of institutional orders on the societal level with the compliance logic being rooted in the orders of the state and the corporation, and the commitment logic as based on the orders of the corporation.The paper ends with a discussion on the how the two logics can influence concrete work environment practices and approaches to management in organizations.